THE PREGNANT MOTHERS’ INTEREST TO CONDUCT HIV TESTING IN SUPPORTING THE PREVENTION OF MOTHER-TO-CHILD HIV TRANSMISSION - Reka Julia Utama; Mahruri Saputra; Ferdi Riansyah (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Human Imunnodefiency Virus (HIV) and Acquired Immunodeficiency Syndrome (AIDS) is a disease that continue to grow and become a global health problem which occurs in both modern and developing countries. HIV transmission can occur through needles and blood transfusions. However, it can occur from HIV-positive mother to their unborn baby. One of the ways which can be conducted by pregnant mother is conducting HIV test during pregnancy. However, there is still a lack of interest in pregnant mothers therefore many mothers do not conduct HIV tests. Whereas the mothers’ interest is highly important to enhance the pregnant mothers’ participation to conduct HIV test. The objective of this research was to investigate the pregnant mothers’ interest in supporting the prevention of mother-to-child transmission at Godean I Health Center, Sleman Yogyakarta. The method of the research was qualitative with phenomenological approach. The informants of this research were taken by using purposive sampling technique, there were 11 informants consisting of 4 pregnant mothers who had conducted HIV test and 6 pregnant mothers who had not conducted HIV test. The result was obtained 4 themes, namely Attitude towered, Subjective norm, Perceived Behavior Control, and the mothers’ interest HIV test. The conclusion is that there are still many mothers who have negative opinions related to HIV testing during pregnancy, and public perception that still considers the taboo regarding HIV testing. The informant conveyed that the support in conducting HIV test came from internal and external factors. The obstacles faced by pregnant mothers in conducting HIV tests are caused by internal and external factors. While for the interest, the majority of pregnant mothers are not interested in taking an.